Effectiveness of a Pedestrian Hybrid Beacon at mid-block pedestrian crossings in decreasing unnecessary delay to drivers and a comparison to other systems - Godavarthy, Ranjit Prasad (Kansas State University, 2010)
Pedestrian signals, particularly at signalized, mid-block crossing can cause delay to drivers after pedestrians’ have successfully crossed, which is termed “unnecessary delay” in this study. In many cases at a mid-block signal, a pedestrian pushes the button and then quickly crosses the street as soon as the walk signal appears and drivers still face several seconds of solid red ball and by law must remain stopped. On a busy street, a queue of vehicles waiting after all pedestrians have crossed can amount to hundreds of hours of unnecessary delay per year. The ‘Pedestrian Hybrid Beacon’ (Initially named a HAWK (High Intensity Activated Crosswalk)) Beacon was proven to be effective in decreasing this unnecessary delay when compared to standard signalized mid-blocks. The City of Lawrence, Kansas was interested in experimenting (as a HAWK beacon was considered experimental when they were installed) with a pedestrian hybrid beacon and they installed their first pedestrian hybrid beacon at a mid-block crossing on 11th street and a second pedestrian hybrid beacon at mid-block crossing on New Hampshire street, Lawrence, Kansas, which were the sites of interest for this research. A study was conducted at these sites to determine the effectiveness of the pedestrian hybrid beacon in decreasing the unnecessary delay to drivers by comparing it to a signalized mid-block crossing on Massachusetts Ave in Lawrence, Kansas. Apart from the delay measurements for these two sites, other parameters such as driver compliance rate to the signal, pedestrian compliance rate, and other driver and pedestrian characteristics were also studied. Video cameras were used to capture video at these sites and the effectiveness of the pedestrian hybrid beacon was analyzed from the video. The HAWK, now in the MUTCD as a Pedestrian Hybrid Beacon, proved to be effective in decreasing the unnecessary delay for drivers in this study. The City of Lawrence had a total of six pedestrian hybrid beacons in operation as per the information received in March 2010.
Keywords: Pedestrian Hybrid Beacon; HAWK; Mid-block Signals; Pedestrians; Engineering, Civil (0543)